Language Disorder Analysis of an Autistic Savant in the Rain Man Movie - Aisyah Siti; Nina Dwiastuty; Amrina Rosyada (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Language is a basic need to our existence of life since speaking, listening, reading, and writing are such fundamental aspects of our daily lives. Those aspects are substantial in establishing social interaction and seizing fabulous achievements as well. However, some people suffered from injured brain, mental retardation, and autism who experienced difficulties such as speech disorder and language disorder. This research was designed to identify types of words utterances and types of language disorder that produced by an autistic savant character in the Rain Man movie. By conducting qualitative research with psycholinguistic approaches, this study revealed the autistic savant characters of the producing utterances, namely articulation disorder, phonological disorder, voice disorder and repetition. By developing people’s knowledge and awareness on the autistic language disorder, this study enlightened people to communicate and understand autistic person in their surroundings and prevented miscommunication as well. Further research is expected to be administered, particularly on an autistic woman to explore comprehensive knowledge and understanding on autistic language disorder.